The Politics of Precaution : Regulating Health, Safety, and Environmental Risks in Europe and the United States - Vogel, David, 1947- (Book collections on Project MUSE., 2012)
The Politics of Precaution examines the politics of consumer and environmental risk regulation in the United States and Europe over the last five decades, explaining why America and Europe have often regulated a wide range of similar risks differently. It finds that between 1960 and 1990, American health, safety, and environmental regulations were more stringent, risk averse, comprehensive, and innovative than those adopted in Europe. But since around 1990, the book shows, global regulatory leadership has shifted to Europe.